A gonadal gap junction INX-14/Notch GLP-1 signaling axis suppresses gut defense through an intestinal lysosome pathway - Zhang, Xiumei; Wang, Yirong; Cai, Zixin; Wan, Zhiqing; Aihemaiti, Yilixiati; Tu, Haijun (Frontiers in Immunology, 2023)
Gap junctions mediate intercellular communications across cellular networks in the nervous and immune systems. Yet their roles in intestinal innate immunity are poorly understood. Here, we show that the gap junction/innexin subunit inx-14 acts in the C. elegans gonad to attenuate intestinal defenses to Pseudomonas aeruginosa PA14 infection through the PMK-1/p38 pathway. RNA-Seq analyses revealed that germline-specific inx-14 RNAi downregulated Notch/GLP-1 signaling, while lysosome and PMK-1/p38 pathways were upregulated. Consistently, disruption of inx-14 or glp-1 in the germline enhanced resistance to PA14 infection and upregulated lysosome and PMK-1/p38 activity. We show that lysosome signaling functions downstream of the INX-14/GLP-1 signaling axis and upstream of PMK-1/p38 pathway to facilitate intestinal defense. Our findings expand the understanding of the links between the reproductive system and intestinal defense, which may be evolutionarily conserved in higher organism.